An effort to improve the quality of human resources through the english short course program for preschool teachers - Mangendre, Yuliana; Laaly, Sri Ayu (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
This training activity focuses on English language training for early childhood teachers in one of sub-districts in Banggai Regency. This study is aimed at increasing the awareness of the importance of introducing English to early childhood, increasing knowledge of English so that it can be taught to students and finding out learning models for early childhood. This service activity was carried out for 4 months from April to July 2023. According to the agreement with partners at the beginning of the meeting, the training time was held twice by using a face-to-face mode for a month, on Saturdays, to be precise in the first and third weeks. This activity ran smoothly from 10.00 am to 12.00 noon. The location for the training was in one of the Educational office in Luwuk Selatan District, Banggai Regency. The Community Service activity involved PAUD (Pendidikan Anak Usia Dini/Early Childhood Education) teachers as the community service partners, consisting of 15 participants representing their respective schools. Training material regarding language components included vocabulary, pronunciation and spelling. The results of this activity showed that the participants were very enthusiastic about participating in the training. This also succeeded in increasing understanding and broadening partners' insights which was expected to be able to pass on to their respective students. It can be concluded from the results of the community activity that the current activity ran successfully. Based on the results of this research, it is recommended that in the future partners always update their knowledge of English through similar training activities and also be able to apply the knowledge gained to their respective students.